Mirroring Society? Tracing the Logic of Diversity in the Canadian Journal of Higher Education - Tamtik, Merli (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2021)
Diversity and equity have become central themes of institutional planning in Canadian post-secondary institutions. The complexity and variance of such activities, and their disconnect from individual experiences, are inherently related to the social norms established by the dominant cultural group. This article argues that published research articles play an important role in reflecting how organizational norms are understood and institutionalized. To trace the normative shifts in how diversity has been addressed in research articles, a systematic analysis of over 186 peer-reviewed articles published in the Canadian Journal of Higher Education between 1971 and 2020 was performed. The findings demonstrate that the concept of diversity has evolved from being examined in narrow binary categories of socio-economic, language, and gender diversity to a more recent focus on intersectionality. The shift from diversity being an issue of individual concern to diversity being a core institu-tional responsibility closely related to student learning is apparent. The article ends with recommendations for future areas of research with specific calls made to increased uptake of critical approaches to diversity for more nuanced perspectives of our accepted social norms in Canadian higher education.